Pematang Johar Creative Village: Developing a Creative Village through Local Wisdom – Based Economic Empowerment - Putri Mentari; Hana Salsabila Lubis; Muhammad Hafiz Abd. Rashid; Khairil Umuri; Teuku Muhammad Syahrizal; Sipnarog Kanchawongpaisan; Mhd Ihsan (Eastasouth Institute, 2025)
This community service program was implemented by lecturers and students if STIE Eka Prasetya in Pematang Johar Village, North Sumatra, in response to the underutilization of local products (various rice, duck egges, tempe, and its derivatives, batik, and recycled crafts) for creative economic development and sustainable tourism. The program aimed to empower the community by strengthening entrepreneurial capacity, product innovation, and the use of local wisdom as the identity of a creative village. The approach used included workshops, participatory training, business mentoring, and hands-on digital marketing practice over one month. As a result, local producers improved product quality and variety, enhanced design and packaging, began using social media for promotion, and developed a better understanding of a basic business management. This program demonstrates the important role of higher education institutions in knowledge transfer and in supporting the development of creative, locally rooted village economies.